Upaya Meningkatkan Kemampuan Kognitif Anak Dengan Mengenalkan Konsep Bilangan Melalui Kartu Angka Di TK Pembina Negeri Sungai Penuh - Oktaviana, Winda; Gusmanto, Rizki (CV. ITTC INDONESIA, 2024)
Of all the students at TK Pembina Negeri Sungai Penuh, only six students (37.5%) have high numeracy skills. To teach children about numbers, the author wants to learn how to make number cards. The TK Pembina Negeri play group was the research population. Kemmis and Taggart's paradigm is used in collaborative classroom action research. Qualitative and quantitative descriptive percentage approaches were included in the data analysis process. Documentation and observation are the methods used to obtain data. There were two rounds of research. includes preparation, action and observation, as well as reflection in each cycle. The research subjects were six tens female students from TK Pembina Negeri Semester I for the 2023–2024 academic year. Research findings show that, with an accuracy rate of 89.2%, children's understanding of numerical concepts is in a good range.